Office‐Based Blue Laser Versus Coblation Therapy for Inferior Turbinate Hypertrophy: A Pilot Study - Abdul‐Latif Hamdan; Zeina Maria Semaan; Lana Ghzayel; Yara Yammine; Jonathan Abou Chaar; Jad Hosri; Patrick Abou Raji Feghali; Anne Marie Daou; Elie Alam (OTO Open, 2025)
Abstract Objective The aim of this pilot study is to compare the effectiveness of office‐based blue laser therapy with coblation therapy in patients with inferior turbinate hypertrophy (ITH). Study Design Retrospective chart review. Setting Tertiary referral center. Methods Patients presenting with nasal obstruction between November 2022 and November 2024, and underwent coblation or blue laser therapy for turbinate reduction were reviewed. Demographic data included age, gender, smoking, history of allergy, history of reflux disease, and history of prior nasal surgery. All patients had filled the nasal obstruction symptom evaluation (NOSE) questionnaire and the visual analog scale (VAS) before and on follow‐up after treatment. Patient's level of comfort during the procedure was also rated using a 10‐point Likert scale with a higher score indicating a greater level of comfort. Results A total of 10 patients underwent office‐based blue laser therapy for turbinate reduction, and 10 patients underwent office‐based coblation of the inferior turbinates. In the subgroup of patients who underwent office‐based blue laser therapy, the mean NOSE score and VAS score decreased significantly (P = .005). In the subgroup of patients who underwent coblation, the mean NOSE score and VAS score decreased significantly (P = .005). When comparing the two subgroups, the difference in the drop of the NOSE score was not statistically significant (P = .198). Similarly, the difference in the drop of VAS score was not statistically significant (P = .280). Conclusion The results of this investigation indicate that both coblation therapy and blue laser therapy are effective office‐based treatment modalities in patients with ITH with comparable results.